Innovation And Good Practices Of Management Studies In Open Distance Learning In Sri Lanka (International Journal of Scientific Research and Management (IJSRM), 2018)
Universities needs to have new strategies be considered as core competency in Education sector. In the face of enormous socio-economic and demographic challenges, Sri Lankan Universities require a more advanced educational performance, providing a better contribution to innovation, competitiveness and economic growth. Universities are currently facing an increasing demand for management graduates, especially in the Open Distance Learning in Sri Lanka. To be ready for the next decade these universities must search to create added value and innovate their institutional models accordingly. In this paper, the open and distance learning providing universities are assessed on their potential to innovate beyond flexible education towards generating new ways of academic and commercial entrepreneurship, including networked initiatives of educational and enterprise incubation. It is evident that universities cannot do without creativity, innovation and entrepreneurship: this is the engine of prosperity not only for universities, but for enterprises, economy and society as a whole